Travel-Associated Salmonella mbandaka Sacroiliac Osteomyelitis in a Healthy Adolescent - Kirsty Le Doare; Elspeth Brooker; Shamez Ladhani (Case Reports in Infectious Diseases)
Pyogenic infections of the sacroiliac joint are rare and usually caused by Staphylococcus aureus. We describe a case of a 16 year-old gymnast who was subsequently diagnosed with Salmonella mbandaka sacroiliac osteomyelitis with adjacent psoas abscess and hepatitis one week after returning from a holiday in Crete. This case highlights a rare presentation of a common travel-associated foodborne infection.